Computer simulation of fatigue, creep and thermal-fatigue cracks propagation in gas-turbine blades - Semenov, Artem (Materiali in tehnologije, 2012)
Methods and computational algorithms for determining the growth rate of fatigue creep and thermal-fatigue cracks are considered. The rate of crack growth is dependent on the stress-intensity factor (or J-integral) for fatigue, on the C*-integral for creep and on the stress-intensity factor (or J-integral) and C*-integral for thermal fatigue. Simulations of the crack propagation under fatigue, creep and thermal fatigue at the edge of the blade of a gas turbine are carried out and discussed.
Keywords: C*-integral; fatigue; creep; utrujenost; thermal fatigue; lezenje; crack; toplotna utrujenost; razpoka; turbine blades; turbinske lopatice; metoda končnih elementov; finite element method; finite element simulation